‫تقييم‬‫ الأصول‬ ‫الثابتة‬ ‫وفق‬ ‫معايير‬ ‫المحاسبة‬ ‫الدولية‬ ‫والنظام‬ ‫المحاسبي‬ ‫المالي‬ ‫"‬‫دراسة‬ ‫مقارنة‬ ‫"‬ - ‬‫هنية ‫بلخير ‬; عبد‬ ‫العزيز ‫ملايكية‬‫‬ (My University, 2021)
The study aims to make a comparison between the valuation of fixed assets in accordance with international accounting standards and the financial accounting system, in knowing the points of compatibility and the differences between the two systems due to their great importance in the budget of the establishment, and this study was supported by a study of land at the Public Economic Enterprise of Road Works of Souk-Ahras which have a study and evaluation of some of its fixed assets has been carried out, we conclude that despite a great lack of mastery of the application of the financial accounting system, or lack of knowledge of some of its concepts and rules due to the habituation of institutions Algerians to the application of the old accounting system, the financial accounting system is highly compatible with international accounting standards for the valuation of fixed assets.